Construction of the technological process and design development of a multifunctional unit for processing vital soybeans with ultrasound. Feasibility of water-crude suspension - D. V. Makarov; F. Ya. Rudik; O. S. Fomenko; V. S. Kutsenkova; A. V. Bannikova (Новые технологии)
Cereals and legumes have a porous structure, being an inert carrier during mass exchange processes; they contain voids in the form of pores and stomata, on the surface of which there are foreign extractable substances in a solid state, in particular, trypsin and urease inhibitor proteins. These substances, due to their harmful effect on the final product, are subject to removal by extraction. One of the methods for inactivating anti-nutritional substances is ultrasonic treatment of soybeans.The article discusses the technology of inactivating inhibitors that worsen food and protein value of vital soybeans. The developed technology was aimed at dissolving a solid substance - soybean inhibitor protein in a liquid, carried out due to molecular diffusion, intensifying the processes of mass transfer and mass return. When creating a suspension by mixing the solid (crushed soybean grain) and liquid (water) phases, water molecules, which are a solvent, penetrate under the action of capillary forces into the pores and stomata of the treated body, begin to penetrate. On this basis, technological directions of research have been established, a sequence has been built and the physical essence of operations has been substantiated, consisting of four main ones - grinding soybean grain, creating a “water-soybean” suspension, ultrasonic (US) treatment of soybeans, drying. As a result of the conducted research, optimal technological parameters have been established for intensifying the process of inactivation of anti-nutritional substances contained in native soybeans: the degree of grinding of soybean grains is 0.5-1.0 mm; the ratio of water-soy suspension (1:1). The efficiency of the developed technological process will be factors affecting the quality of the resulting products, the duration and energy intensity of the process, resource conservation, simplicity of design and low cost of manufacture, the possibility of automation.